A STUDY ON ACTIVITY BASED COSTING IN ELGI ELECTRIC AND INDUSTRIES LTD - SV , Elumalaiyan; R , Bharthvajan; M., Radhikaashree (International Journal of Psychosocial Rehabilitation, 2020)
The title is “A Study on Activity-Based Costing in ELGI Electric and Industries Ltd.". This helped the researcher learn about activity-based costing and its benefits to the organization. The study aims to determine the benefits of ABC implementation in the motor division of the company. This study studied the reduction in the cost because of implementing ABC and found out the area where deviations were found.